Melawan Radikalisme di Media Sosial: Kampanye Moderasi Beragama Melalui Media Online di Indonesia - Setia, Paelani; Haq, Mochamad Ziaul (Parahyangan Catholic University, 2023)
This paper will discuss online media sites implementing religious moderation campaigns in Indonesia. The case study in this paper is the online media Harakatuna.com. The research method is qualitative, collecting data through virtual ethnography or online observations of the Harakatuna.com media page and Harakatuna Media's Instagram, Twitter, and Facebook social media accounts. This research found that it is not appropriate if the religious moderation campaign has only been carried out through conventional methods such as seminars, recitations, and workshops. Therefore, Harakatuna.com is present as a campaign agent for religious moderation by taking a role in social media. Consequently, Harakatuna.com carries out counter-narrative radicalism by introducing peaceful religious moderation in Indonesia with digital methods such as webinars, scientific publications, and opinion writing. Furthermore, Harakatuna.com also carries out a counter-ideological role against the Khilafahism ideology that Hizbut Tahrir Indonesia (HTI) echoes. Harakatuna.com carries out the counter-ideology through the Pancasila ideology campaign as the foundation of the nation and state by the values of religious teachings, including Islam. The roles carried out by Harakatuna.com are the actualization of the concept of a Cyber Islamic Environment, a new virtual world environment that can be used for the benefit of Muslims, one of which is the delivery of messages of religious moderation.